Excitability of Rat Superficial Dorsal Horn Neurons Following a Neonatal Immune Challenge - Tadros, Melissa A.; Zouikr, Ihssane; Hodgson, Deborah M.; Callister, Robert J. (Frontiers in Neurology, 2018)
Previous studies have shown that neonatal exposure to a mild inflammatory challenge, such as lipopolysaccharide (LPS, Salmonella enteriditis) results in altered pain behaviours later in life. To further characterise the impact of a neonatal immune challenge on pain processing, we examined the excitability of superficial dorsal horn (SDH) neurons following neonatal LPS exposure and subsequent responses to noxious stimulation at three time-points during early postnatal development. Wistar rats were injected with LPS (0.05 mg/kg i.p.) or saline on postnatal days (PNDs) 3 and 5, and later subjected to the formalin test at PNDs 7, 13 and 22. One hour after formalin injection into the plantar hindpaw, animals were euthanized (Ketamine, 100 mg/kg i.p.) and transverse slices from the lumbosacral spinal cord were prepared. Whole-cell patch-clamp recordings were made from SDH neurons (KCH3SO4-based internal, 22-24oC) on the ipsi- and contralateral sides of the spinal cord. Depolarising current steps were injected into SDH neurons to categorize action potential (AP) discharge. In both saline- and LPS-treated rats we observed age-related increases the percentage of neurons exhibiting tonic- and delayed-firing, with concurrent decreases in single-spiking, between PND 7 and 22. In contrast, neonatal exposure to LPS failed to alter the proportions of AP discharge patterns at any age examined. We also assessed the subthreshold currents that determine AP discharge in SDH neurons. The rapid outward potassium current, IAr, dominated at all three time-points, however, its prevalence decreased with age. Peak IAr current amplitude was greater in ipsilateral versus contralateral SDH neurons from LPS-treated rats. Spontaneous excitatory synaptic currents (sEPSCs) were recorded to assess network excitability. Age-related increases were observed in sEPSC frequency and time course, but not peak amplitude, in both saline- and LPS-treated rats. Furthermore, sEPSC frequency was higher in ipsilateral versus contralateral SDH neurons in LPS-treated animals. Together, these data suggest that although baseline excitability of SDH neurons remains relatively stable following neonatal exposure to LPS, there are subtle, but potentially important, differences in the susceptibility of SDH neurons to noxious inflammatory stimuli later in life. This provides a possible mechanism through which neonatal LPS exposure enhances pain responses later in life.